PINK1-Dependent Mitophagy Reduced Endothelial Hyperpermeability and Cell Migration Capacity Under Simulated Microgravity - Li, Chengfei; Pan, Yikai; Tan, Yingjun; Wang, Yongchun; Sun, Xiqing (Frontiers in Cell and Developmental Biology, 2022)
The cardiovascular dysfunction including orthostatic intolerance and disability on physical exercise is one of the health problems for astronauts induced by long term spaceflight. As an important part of vascular structure, the vascular endothelium, uniquely sensitive to mechanical force, plays a pivotal role in coordinating vascular functions. Our study found that simulated microgravity induced PINK1-dependent mitophagy in human umbilical vein endothelial cells (HUVECs). Here, we explored the underlying mechanism of mitophagy induction. The ER stress induced by proteostasis failure in HUVECs promoted the Ca2+ transfer from ER to mitochondria, resulting in mitochondria Ca2+ overload, decreased mitochondrial membrane potential, mitochondria fission, accumulation of Parkin and p62 in mitochondria and mitophagy under simulated microgravity. Moreover, we assumed that mitophagy played a vital role in functional changes in endothelial cells under simulated microgravity. Using mdivi-1 and PINK1 knockdown, we found NLRP3 inflammasome activation was enhanced after mitophagy was inhibited. NLRP3 inflammasome contributed to endothelial hyperpermeability and cellular migration via releasing IL-1β. Thus, mitophagy inhibited cell migration ability and hyperpermeability in HUVECs exposed to clinostat simulated microgravity. Collectively, we here clarify the mechanism of mitophagy induction by simulated microgravity in vitro and demonstrate the relationship between mitophagy and vascular endothelial functional changes including cellular migration and permeability. This study deepens the understanding of vascular functional changes under microgravity.